Conceptual Design of a Permissioned Blockchain-Based Asset Management System in Higher Education using Hyperledger Fabric - Ichwan Subekti; Irman Hermadi; Yani Nurhadryani (Journal of Information System and Informatics, 2026)
Effective asset management is a fundamental pillar of higher education operations and strategic sustainability. However, existing conventional systems are often hampered by systemic challenges, including operational inefficiencies, lack of transparency, and chronic data integrity issues resulting from fragmented information silos. This study proposes a conceptual design for a higher education asset management system utilizing blockchain technology to address these governance weaknesses. Based on a comprehensive literature review and system architecture modeling, this study synthesizes concepts from asset management, blockchain principles, and enterprise platforms without deploying a functional prototype. The proposed conceptual framework is built on a permissioned blockchain platform, specifically Hyperledger Fabric, and adopts a multi-layered system architecture for modularity. To balance data integrity with storage efficiency, the system conceptually applies a hybrid data storage pattern combining on-chain ledger records and off-chain databases. Furthermore, the business logic is modeled into smart contracts (chaincode) to automate and secure all stages of the asset lifecycle, from procurement to disposal. The study proposes a theoretical blueprint designed to provide a single, immutable source of truth and enforce multi-level digital approvals. The impact of this research offers a conceptual architectural blueprint that aims to shift academic asset management from a reactive administrative task to an automated, transparent governance ecosystem, paving the way for future validation tasks including performance, scalability, usability, and organizational feasibility.